2009
DOI: 10.1002/jcb.22350
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells: Cell culture, markers, and targets for new therapies

Abstract: A cancer stem cell is defined as an undifferentiated cell with the ability to self-renew, differentiate to multiple lineages and initiate tumors that mimic the parent tumor. In this review, we focus on glioblastomas, describing recent progress and problems in characterizing these cells. There have been advances in cancer stem cell culture, but tumor cell heterogeneity has made purification of cancer stem cells difficult. Indeed, it may be that cancer stem cells significantly vary from tumor to tumor. We also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
170
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 70 publications
(83 reference statements)
3
170
0
5
Order By: Relevance
“…CSCs play an important role in tumor progression (3,15). To confirm whether the effect of forced Nanog expression on HeLa cell malignant behavior is associated with CSCs, we tested the tumor sphere forming ability of HeLa-Nanog cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs play an important role in tumor progression (3,15). To confirm whether the effect of forced Nanog expression on HeLa cell malignant behavior is associated with CSCs, we tested the tumor sphere forming ability of HeLa-Nanog cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) appear to be responsible for tumor initiation, progression and resistance to conventional treatment (2,3). Nanog is one of the core transcription factors for maintaining the stemness of embryonic stem cells (ESCs) (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that they be isolated by several ways including surface marker sorting (Al-Hajj et al, 2003;Singh et al, 2004), side-population cells selecting (Hadnagy et al, 2006;Moserle et al, 2010), and mammosphere cultures (Ponti et al, 2005;Yu et al, 2008). Most CSCs form clones when nurtured in low adhesive vessels (Chumsri and Burger, 2008;Kobayashi et al, 2008;Gilbert and Ross, 2009), and further generate sphere clones in the present of growth factors such as epidermal growth factor (EGF). Therefore the sphere clone formation assay has been widely used for the separation and identification of CSCs (Ponti et al, 2005;Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Due to possessing a strong drug tolerance, CSCs are not easily destroyed, which leads to the failure of treatment. Therefore, a key goal for tumor therapy is to effectively induce the apoptosis of tumor stem cells (23).…”
Section: Discussionmentioning
confidence: 99%